I am multiplying radicals and I have a question like this:
square root of ((6x^7)(y^3)) multiplied by square root of ((7x^3)(y^-1))
In the end I got x^(5)y(square root of 42)
Does this look right at all?
Hello, cjh824!
Simplify: .$\displaystyle \sqrt{6x^7y^3}\cdot\sqrt{7x^3y^{-1}}$
In the end I got: .$\displaystyle x^5y\sqrt{42}$ . . . . Right!
$\displaystyle \sqrt{6x^7y^3}\cdot\sqrt{7x^3y^{-1}} \;=\;\sqrt{(6x^7y^3)(7x^3y^{-1})}$
. . $\displaystyle =\;\sqrt{42x^{10}y^2} \;=\;\sqrt{42}\cdot\sqrt{x^{10}}\cdot\sqrt{y^2} \;=\;x^5y\sqrt{42}$